Robot Path Planning with Cellular Neural Network - Zhong, Yongmin; Shirinzadeh, B.; Yuan, X. (IGI Global, 2010)
This paper presents a new methodology based on neural dynamics for optimal robot path planning by drawing an analogy between cellular neural network (CNN) and path planning of mobile robots. The target activity is treated as an energy source injected into the neural system and is propagated through the local connectivity of cells in the state space by neural dynamics. By formulating the local connectivity of cells as the local interaction of harmonic functions, an improved CNN model is established to propagate the target activity within the state space in the manner of physical heat conduction, which guarantees that the target and obstacles remain at the peak and the bottom of the activity landscape of the neural network, respectively. The proposed methodology can not only generate real-time, smooth, optimal and collision-free paths without any prior knowledge of the dynamic environment, without explicitly searching over the global free work space or searching collision paths, and without any learning procedures, but it can also easily respond to the real-time changes in dynamic environments. Further, the proposed methodology is parameter-independent and has an appropriate physical meaning.